Early implant‐associated osteomyelitis results in a peri‐implanted bacterial reservoir. Issue 1 (5th October 2016) - Jensen, Louise Kruse; Koch, Janne; Aalbæk, Bent; Moodley, Arshnee; Bjarnsholt, Thomas; Kragh, Kasper Nørskov; Petersen, Andreas; Jensen, Henrik Elvang
Abstract : Implant‐associated osteomyelitis (IAO) is a common complication in orthopedic surgery. The aim of this study was to elucidate how deep IAO can go into the peri‐implanted bone tissue within a week. The study was performed in a porcine model of IAO. A small steel implant and either 10 4 CFU/kg body weight of Staphylococcus aureus or saline was inserted into the right tibial bone of 12 pigs. The animals were consecutively killed on day 2, 4 and 6 following implantation. Bone tissue around the implant was histologically evaluated. Identification of S. aureus was performed immunohistochemically on tissue section and with scanning electron microscopy and peptide nucleic acid in situ hybridization on implants. The distance of the peri‐implanted pathological bone area (PIBA), measured perpendicular to the implant, was significantly larger in infected animals compared to controls (p = 0.0014). The largest differences were seen after 4 and 6 days of inoculation, where PIBA measurements of up to 6 mm were observed. Positive S. aureus bacteria were identified on implants and from 25 μm to 6 mm into PIBA. This is important knowledge for optimizing outcomes of surgical debridement in osteomyelitis.